Ad Agency Leadership in the US, UK, and Australia: A Mixed-Method Analysis of Effective Attributes and Styles. Issue 2 (15th March 2022) - Patwardhan, Padmini; Kerr, Gayle; Patwardhan, Hemant; Kelly, Louise; Habib, Sabrina; Mortimer, Kathleen; Laurie, Sally
Abstract: Unlike the extensive scholarship on leadership in related disciplines, research on leadership in advertising is almost nonexistent. This study investigates practitioner views on attributes and styles of effective agency leaders in the US, UK, and Australia using GLOBE's (Global Leadership and Organizational Behavior Effectiveness) Culturally Endorsed Leadership Theory. All three regions are part of GLOBE's Anglo cultural cluster. The research examines whether the theory's central proposition—that leadership in global contexts has universally endorsed elements but is also culturally contingent—is valid in an advertising setting. Using a mixed-method approach, data were collected from agency staff and leaders via 255 survey responses and 40 in-depth interviews. Findings indicate that the best leaders are seen as people-focused, collaboration-driven, and future-oriented. Integrity, vision, and inspiration are top leadership attributes, with collaborative and performance-oriented leadership styles considered the most effective. Views were fairly consistent across regions, with some nuanced differences. One interesting difference from main GLOBE findings is the emphasis on soft skills as a core component of effective leadership. Future research should examine this further, as well as the relationship between leadership and agency culture, millennial and gender differences, and leadership training challenges and also examine advertising leadership across other GLOBE cultural clusters.